The Effects of an In-vehicle Collision Warning System on Older Drivers' On-road Head Movements at Intersections - Shichrur, Rachel; Ratzon, Navah Z.; Shoham, Arava; Borowsky, Avinoam (Frontiers in Psychology, 2021)
Abstract: With age might come a decline in crucial driving skills. The effect of a collision warning system (CWS) on older drivers’ head movements behavior at intersections was examined. Methods: 26 old-adults, between 55-64 years of age, and 16 Older drivers between 65-83 years of age, participated in the study. A CWS (Mobileye Inc.) and a front-back in-vehicle camera (IVC) were installed in each of the participants’ own vehicles for six months. The CWS was utilized to identify unsafe events during naturalistic driving situations, and the IVC was used to capture head direction at intersections. The experimental design was conducted in three phases (baseline, intervention, and carryover), two months each. Unsafe events were recorded by the CWS during all phases of the study. In the second phase, the CWS feedback was activated to examine its effect on drivers' head movement' behavior at intersections. Results: Older drivers (65+) drove significantly more hours in total during the intervention phase (M = 79.1hrs., SE = 10) than the baseline phase (M = 39.1hrs., SE = 5.3) and the carryover phase (M = 37.7hrs., SE = 5.4). The study revealed no significant differences between the head movements of older and old-adult drivers at intersections. For intersection on the left direction, a significant improvement in drivers' head movements' behavior was found at T-junctions, turns and four-way intersections from phase 1 to phase 3 (p < .01), however, two intersection types presented a decrease along the study phases. The head movements' behavior at roundabouts and merges was better at phase 1 compared to phase 3 (p < .01). There was no significant reduction of the mean number of CWS unsafe events across the study phases. Conclusions: The immediate feedback provided by the CWS was effective in terms of participants’ head movements at certain intersections but was harmful in others. However, older drivers drove many more hours during the active feedback phase, implying that they trusted the system. Therefore, in the light of this complex picture, using the technological feedback with older drivers should be followed with an additional mediation or follow-up to ensure safety.